2018
DOI: 10.1007/s00436-018-5875-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization and functional analysis of Eimeria tenella malate dehydrogenase

Abstract: Eimeria tenella is a serious intracellular parasite that actively invades cecal epithelial cells of chickens. The widespread use of drugs causes severe resistance to Eimeria tenella. We detected that malate dehydrogenase (MDH), one of the differentially expressed genes, was upregulated in diclazuril-resistant and maduramicin-resistant strains through transcriptome sequencing. In this study, we cloned and expressed MDH of E. tenella (EtMDH). Quantitative real-time polymerase chain reactions (qPCR) and Western b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…2019) using rabbit anti‐ E. tenella sporozoite serum (Chen et al. 2018) (dilutions 1:100) or mouse monoclonal anti‐GST tag antibody (Beyotime, 1:2,000 dilution) as the primary antibodies. Determinations of the purified protein concentrations were performed using the BCA protein assay kit (Beyotime, Haimen, China).…”
Section: Methodsmentioning
confidence: 99%
“…2019) using rabbit anti‐ E. tenella sporozoite serum (Chen et al. 2018) (dilutions 1:100) or mouse monoclonal anti‐GST tag antibody (Beyotime, 1:2,000 dilution) as the primary antibodies. Determinations of the purified protein concentrations were performed using the BCA protein assay kit (Beyotime, Haimen, China).…”
Section: Methodsmentioning
confidence: 99%
“…Chemical synthetic drugs include a wide range, such as sulfachloropyrazine sodium, amproline, toltrazuril, clopidol, and nicarbazine ( Greif et al . , 2001 ; Chen et al . , 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Based on our preliminary results, we speculated that the ChTLR15/ChNF-κB-ChNLRP3/ChIL-1β signaling pathway may be specifically activated by Eimeria sporozoites, which mediate inflammatory injury during Eimeria infection. It was reported that chicken embryo fibroblast cells (DF-1) can be directly invaded by Eimeria sporozoites and have been extensively applied to study innate immune responses [15][16][17]. To verify the above hypothesis, the ChTLR15/ChNF-κB and ChNLRP3/ChIL-1β signaling pathways were analyzed in DF1 cells at the transcriptional and protein levels using small interfering RNA (siRNA) and overexpression technology.…”
Section: Introductionmentioning
confidence: 99%